2013
DOI: 10.1016/j.vhri.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Costo-Efectividad de la Proteína C Reactiva, Procalcitonina y Escala de Rochester: Tres Estrategias Diagnosticas para la Identificación de Infección Bacteriana Severa en Lactantes Febriles sin Foco

Abstract: C reactive protein is the strategy more cost-effective to detect SBI in children with Fever without Source in Argentina. Due to low proportion of correctly diagnosed cases (< 80%) of three tests in the literature and our study, however; an individualized approach for children with fever is still necessary to optimize diagnostic investigations and treatment in the different emergency care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The panorama in the comparative studies, where most patients come after 4–6 h of the start of symptoms, is not different from the real life providing greater external validity to our results [ 24 ]. We previously published an economic evaluation of these same three tests in Argentina in 2013 [ 7 ]. This study found small differences between CPR and PCT with respect to their cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The panorama in the comparative studies, where most patients come after 4–6 h of the start of symptoms, is not different from the real life providing greater external validity to our results [ 24 ]. We previously published an economic evaluation of these same three tests in Argentina in 2013 [ 7 ]. This study found small differences between CPR and PCT with respect to their cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…PCT offers better specificity than CRP to detect SBI with an early detection possible of SBI if the evolution of the fever is < 12 h [ 6 ]. However, their cost limited their use in developing countries [ 7 , 8 ]. Economic evaluations are tools that provide objective information to decision-makers regarding the inclusion of new diagnostic tests in health insurance plans.…”
Section: Introductionmentioning
confidence: 99%